Developing Digital Interventions: A Methodological Guide. (4th February 2014) - Bradbury, Katherine; Watts, Sam; Arden-Close, Emily; Yardley, Lucy; Lewith, George
Abstract : Digital interventions are becoming an increasingly popular method of delivering healthcare as they enable and promote patient self-management. This paper provides a methodological guide to the processes involved in developing effective digital interventions, detailing how to plan and develop such interventions to avoid common pitfalls. It demonstrates the need for mixed qualitative and quantitative methods in order to develop digital interventions which are effective, feasible, and acceptable to users and stakeholders.